Pendidikan Islam Pada Penderita AIDS di Kecamatan Trucuk Kabupaten Bojonegoro - Ulva Badi' Rohmawati (Halaqa: Islamic Education Journal, 2018)
The religion with an unknown number of functions of spiritual functions, psychological functions and social functions. The spiritual function is related to our peace and one's beliefs. Psychological functions are related to remembering someone who can increase one's degree. Social functions are related to human interaction with each other. These three functions can be conveyed and embedded in the heart through Islamic education. Religion does not only occur in formal education institutions, but for Islamic education can survive around the family and in reality sometimes not all religious functions can be done well. For example in the community, people with AIDS (PLWHA), most people judge them with negative ratings. This negative assessment sometimes makes a person not good, even worse. In this study examined how Islamic education in PLWHA (HIV/AIDS sufferers). Basically, Islam teaches about: Aqeedah, shari'ah, morality. This study discusses the faith and practice of worshiping AIDS patients in Trucuk District. In this study using a phenomenological qualitative research approach. Associated with religious education ODHA (people with HIV AIDS) are different. This depends on the background of PLWHA. Most of them understand Islamic teachings from aspects of aqeedah, shari'ah, and morality.